2011
DOI: 10.1182/blood-2010-12-325712
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of CCAAT/enhancer–binding protein α promotes the biased primitive hematopoiesis of zebrafish

Abstract: Hematopoiesis is evolutionarily conserved from zebrafish to mammals, and this includes both primitive and definitive waves during embryogenesis. Primitive hematopoiesis is dominated by erythropoiesis with limited myelopoiesis. Protein sumoylation, a ubiquitination-like posttranslational protein modification, is implicated in a variety of biochemical processes, most notably in transcriptional repression. We show here that the loss of 6 small ubiquitin-related modifier (SUMO) paralogs triggers a sharp upregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…In addition to the transcriptional regulation, post-translational modifications are also important for myeloid-erythroid lineage choice. It has been reported that hyposumoylation of C/ebpα a leads to expansion of myeloid lineage at the expense of erythroid lineage, suggesting that sumoylation of C/ebpα is important for the differentiation control of erythroid-myeloid progenitors [60]. In this study, we demonstrated that jmjd3 bias the myeloid commitment at the expense of the erythroid commitment.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the transcriptional regulation, post-translational modifications are also important for myeloid-erythroid lineage choice. It has been reported that hyposumoylation of C/ebpα a leads to expansion of myeloid lineage at the expense of erythroid lineage, suggesting that sumoylation of C/ebpα is important for the differentiation control of erythroid-myeloid progenitors [60]. In this study, we demonstrated that jmjd3 bias the myeloid commitment at the expense of the erythroid commitment.…”
Section: Discussionsupporting
confidence: 58%
“…As our previous studies demonstrated that lack of sumoylation biased primitive hematopoiesis9, here we questioned its role in definitive hematopoiesis. To evaluate the effects of sumoylation on definitive hematopoietic development, the temporal and spatial expression patterns of a panel of HSPC and lineage-specific markers were examined by whole-mount mRNA in situ hybridization (WISH) after antisense MO-mediated knock-down.…”
Section: Resultsmentioning
confidence: 99%
“…Both C/ebpα-deficient fetal and adult HSPCs exhibit enhanced proliferation and competitive repopulation activities212224, whilst activation of C/ebpα in HSPCs leads to their reduced self-renewal and proliferation23. We have previously shown that zebrafish C/ebpα can be sumoylated, triggering transcriptional repression9. Thus, herein we investigated the potential role of C/ebpα sumoylation in the regulation of HSPC homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations